Uruguay : Central Bank Transparency Code Review. (IMF Staff Country Reports; Country Report, 2022)
The Central Bank of Uruguay (BCU) is implementing transparency practices that are broadly aligned with the good practices for central banks (Table 1). The institution's comprehensive communication tools and strategy underpin the commitment to transparency and its accountability for the price stability and financial system soundness mandates. In addition, the adoption of transparency among its value statements supports its mission "to contribute to the wellbeing of the society." The BCU management wants to make further improvements in the transparency practices and envisions that by relying on its strong legal and institutional arrangements this can be achieved. Ultimately, the BCU intends to be recognized as an "independent, effective, and reliable institution with the capability to anticipate and respond to new challenges."